THE ANALYSIS OF THE TEACHER’S STRATEGIES IN TEACHING AND THE STUDENTS’ INTEREST IN READING IN CLASS IX AT SMPN 5 CAMPLONG - Andi Rizkillah (Language-Edu, 2020)
Reading is being one of the important activities in order to obtain knowledge because there are a lot of information that can be acquaired through written media and can add the learners’ vocabulary. The purpose of this research are (1) to find the teacher’s strategies in teaching reading and (2) to find the students’ interest factors in learning reading. The method of this research was descriptive qualitative method. Through this method, the researcher analyzed the strategies that used by the teacher in teaching and the interest factors of the students in learning reading in class IX at SMPN 5 Camplong. The techniques used in this research to collecting data were observation, questionaire, and interview. The result of this research showed that in teaching reading the teacher used some strategies, there are: (1) 3 phase technique, (2) scaffolding, and (3) think aloud. While the students’ interest factors are caused by: (1) students’ previous experience, (2) teacher values, (3) understandable subject.